infection in patients with Kawasaki disease - Mi Na Lee; Jie Hae Cha; Hye Mi Ahn; Jeong Hyun Yoo; Hae Soon Kim; Sejung Sohn; Young Mi Hong (Korean Pediatric Society, 2011)
PurposeKawasaki disease (KD) is the main cause of acquired heart disease in children. In addition to cardiovascular involvement, many complications have been recognized in KD. However, respiratory complications have been rarely reported. We investigated the differences in clinical characteristics, laboratory findings, radiography findings, and echocardiography findings of Mycoplasma pneumoniae infection and other types of pneumonia in KD patients.MethodsAmong 358 patients with KD, 54 developed concurrent pneumonia. Among the 54 patients, 12 (22.2%) with high titers of anti-M. pneumoniae antibody (AMA) (>1:640) were grouped in the M. pneumoniae group and 42 were included in the control group. Serum AMA was measured in each patient. Clinical laboratory findings and total duration of fever were analyzed.ResultsThe duration of fever, serum hemoglobin, white blood cell count, platelet count, erythrocyte sedimentation rate, C-reactive protein level, albumin level, and the incidence of coronary arterial lesions showed no statistical difference in the 2 groups. Neutrophil count was significantly higher in the M. pneumoniae group than in the control group. Among various radiography findings observed in pneumonia, consolidation and pleural effusion were more frequent in the M. pneumoniae group than in the control group. On the other hand, parahilar peribronchial opacification, diffuse interstitial lesion, and normal findings prevailed in the control group.ConclusionKD patients can have concurrent infections, especially pulmonary symptoms. The cause of KD is likely to be associated with M. pneumoniae infection. Thus, immediate treatment of M. pneumoniae infection in KD patients is very important.